THE INFLUENCE OF EWOM THROUGH INSTAGRAM SOCIAL MEDIA ON ONLINE PURCHASE INTENTION OF PRODUCTS: STUDY IN THE CITY OF BATAM - Catheline Catheline; Didi Sundiman (STKIP Singkawang, 2019)
In general, this study aims to determine the effect of eWOM through social media Instagram on the purchase intention of products online in Batam City. This study uses a quantitative approach. The sample in this study amounted to 113 respondents who were users of social media Instagram. This research instrument using a questionnaire and analyzed using techniques Structural Equation Modeling (SEM) with the help of the SmartPLS 2.0 program. The results of this study indicate that trust, informational influence, moral obligation have significant involvement in eWOM, but the altruism variable does not have a significant effect on eWOM through social media Instagram and eWOM through social media Instagram has a strong influence on purchase intention of products online in Batam City. Based on the results of this study, it can be concluded that the exchange of information through eWOM can lead to consumer buying interest.